Motywy wyboru klas mundurowych przez młodzież w kontekście społeczno-edukacyjnym - Rogowicz, Dariusz; Sapun, Marcin (Studia Edukacyjne, 2025)
The aim of the article is to identify and analyze the motives and psychological and sociological conditions accompanying young people’s decisions to choose uniformed classes within the Polish education system. The study verifies the assumption that this choice is primarily associated with internal developmental needs characteristic of adolescence rather than with pragmatic considerations related to future occupational security. The analysis is based on the results of a survey conducted among 282 students and graduates of uniformed classes from the Opole Voivodeship. Quantitative data were subjected to statistical analysis, including correlation and significance tests, to verify five research hypotheses. The findings were additionally confronted with data on the professional motivations of uniformed service officers and nationwide studies on social trust. The interpretation, grounded in motivational psychology, indicates that the dominant motives for choosing uniformed classes are internal in nature, such as interest in uniformed services, the desire to acquire new skills, and the need to experience challenges and adventure. The hypothesis linking this educational choice with the need for security was rejected, which supports the concept of a “romantic phase” of motivation typical of adolescence, distinct from the “pragmatic phase” observed among adult officers. Sociological analysis confirms that students of uniformed classes predominantly originate from smaller towns and rural areas. While the influence of family tradition was not statistically confirmed, the educational institution itself emerged as a key factor in transforming youthful aspirations into concrete career plans. The decision to choose a uniformed class appears to be a multidimensional process in which psychological needs related to development, identity formation, and belonging co-occur with a specific sociological context shaped by place of residence, family support, school ethos, and the social image of uniformed services. The results highlight the theoretical value of the motivational mechanisms identified and suggest the need to differentiate recruitment strategies, addressing adolescents and adult candidates with distinct communication approaches.